Analisis Kadar Karbohidrat, Lemak Dan Protein Dari Tepung Biji Mangga (Mangifera indica L) Jenis Gadung - Qalsum, Umi; Diah, Anang Wahid M.; Supriadi, Supriadi (Jurnal Akademika Kimia, 2015)
Mango (Mangifera indica L) seeds never to used, so they need efforts to be as food ingredients such as flour. Gadung mango seed was one type of mango seeds used as flour. This study aims to determine the nutrient content i.e. carbohydrates, fats, and proteins of Gadung mango seed flour produced through sulfurization and without sulfurization. Sodiumbisulfite (NaHSO3) with a concentration of 730 ppm was used for mango seed soak for 4 hours at sulfurization stage. The results showed that the Gadung mango seed flour through sulfurization had levels of 13.89% carbohydrate, 12.94% fat and 8.48% protein, while the mango seed flour without sulfurization had levels of 20% carbohydrate, 14.83% fat, and 4.84% protein. The technique of sulfurization on making mango seed flour can reduce levels of carbohydrates and fats as well as maintaining the protein content.